Geometry of Low-dimensional Manifolds 1: Gauge Theory and Algebraic Surfaces - Donaldson, S. K (Cambridge, 2013)
This is perhaps a rather technical result, but it had been isolated by Gromov in 1970 as the crux of a comprehensive "hard versus soft" alternative in "symplectic topology": Gromov showed that if this rigidity result was not true then any problem in symplectic topology (for example the classification of symplectic structures) would admit a purely algebro-topological solution (in terms of cohomology, characteristic classes, bundle theory etc.) Conversely, the rigidity result shows the need to study deeper and more specifically geometrical phenomena, beyond those of algebraic topology.